2019
DOI: 10.1093/ntr/ntz162
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Reduction in Cigarettes: Literature Review and Gap Analysis

Abstract: Background The US Food and Drug Administration (FDA) is considering reducing nicotine levels in cigarettes to “minimally or non-addictive levels.” However, important research gaps remain, and the FDA must determine when the available research is sufficient to support moving forward. Methods The authors conducted a systematic review of research articles in PubMed relating to nicotine reduction. Building on a review of risk ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 96 publications
2
25
0
Order By: Relevance
“…Our results are consistent with those of other human laboratory findings, where VLNCs reduce craving and withdrawal and delay the onset of subsequent preferred tobacco self‐administration 8,9,20 . Our findings also support evidence from clinical trials, where switching to VLNCs is associated with reduced craving/withdrawal, increased cessation success and reduced relapse 5,46 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with those of other human laboratory findings, where VLNCs reduce craving and withdrawal and delay the onset of subsequent preferred tobacco self‐administration 8,9,20 . Our findings also support evidence from clinical trials, where switching to VLNCs is associated with reduced craving/withdrawal, increased cessation success and reduced relapse 5,46 …”
Section: Discussionsupporting
confidence: 91%
“…Reducing cigarette nicotine content to nonreinforcing levels may reduce addiction severity and facilitate smoking cessation 3,4 . In clinical trials, very low nicotine content cigarettes (VLNCs; ≤0.4 mg/g of nicotine) can reduce exposure to nicotine, smoking quantity and dependence severity and increase cessation attempts and success, 5,6 with minimal evidence of harm, such as compensatory smoking (i.e., increasing smoking to maintain desired nicotine levels) 7 . In laboratory research, VLNCs alleviate abstinence‐induced craving and withdrawal and delay the onset of subsequent smoking 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been made clear that in order to mitigate any negative consequences, the availability of regulated alternative nicotine products is important and protective measures to reduce the use of illegal cigarettes need to be implemented. Although several gaps in research have been identified, some of these gaps are currently being addressed and, as stated by Berman and Glasser, 26 “given the overwhelming amount of harm caused by combusted tobacco products and the substantial and rapidly growing body of literature on nicotine reduction, the remaining research gaps should not prevent the FDA from moving forward with the rulemaking process.”…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Berman and Glasser’s 26 literature review summarized the state of the science and identified gaps, which include the need for more studies that better reflect the availability and use of a wide variety of tobacco and nicotine products (including cigarettes from illegal markets) and the potential for dual or multiproduct use, that model the impact of a nicotine standard in the context of other control measures, and that determine the impact of product standards on cessation, initiation and relapse.…”
Section: Reactions To a Potential Nicotine Reduction Policy And Reseamentioning
confidence: 96%
“…Initial ideas for a nicotine reduction strategy involved gradually reducing the allowable level of nicotine in cigarettes to non-addicting levels, both as a way to prevent youth from becoming addicted and to help existing smokers to quit 3 . A growing body of small experimental studies suggests that removing nicotine from cigarettes may assist smokers to successfully quit, but no large-scale interventions, under real-world conditions, have yet been conducted 4 . Nonetheless, there is some interest in exploring possible policy solutions to reducing the addictiveness of tobacco products, especially given the current proliferation of novel and alternative nicotine and tobacco products.…”
mentioning
confidence: 99%